SISTEM INFORMASI RENCANA STUDI BERBASIS WEB ONLINE STUDI KASUS SEKOLAH TINGGI ILMU KOMPUTER CIPTA KARYA INFORMATIKA - Veri Arinal (CKI ON SPOT, 2017)
Information Systems Study plan is an information system used to handle problems related to the management of teaching and learning planning conducted in schools or colleges to monitor the things that have been achieved during the learning process. This paper develops a web-based online information system that allows access to be done easily and quickly in real-time without constrained space, time and devices. The system was developed using the CodeIgniter Framework which is a PHP framework using Model-View-Controller or MVC and as data storage used MYSQL database. Good and friendly user interface design for each user will be able to solve academic problems for college students as access to real-time artificial information.